Benchmarking Para Servicios de Agua - Dane, Peter (IWA Publishing, 2011)
"Benchmarking has become a key tool in the water industry to promote and achieve performance targets for utilities. The use of this tool for performance improvement through systematic search and adaptation of leading practices, has expanded globally during the past decade. Many ongoing projects worldwide aim to address different needs and objectives, in varying contexts, with outstanding results and impact. Benchmarking Water Services provides valuable information to everyone interested in benchmarking in the water industry. The text is aimed at utilities considering joining a benchmarking project, experienced practitioners in charge of organizing a benchmarking exercise, consultants, regulators and researchers. The document is presented with a clear practice oriented approach and can be used as a how-to-benchmark guide presented from different perspectives (participants, organizers, supervising bodies). Readers will gain practical insight on real life benchmarking practices and will benefit from the experiences gained in some of the leading benchmarking projects of the water industry (including the IWA-WSAA benchmarking efforts, the European Benchmarking Co-operation and the several benchmarking projects carried out in Austria and Central Europe). The manual also presents the new IWA Benchmarking Framework, which aims to harmonize the terms used to describe benchmarking and performance indicators practices in the water industry, guaranteeing a more fluent and efficient communication. This Manual of Best Practice is edited by the IWA Specialist Group on Benchmarking and Performance Assessment, and co-published by AWWA and IWA Publishing. ----- Praise for Benchmarking Water Services: ""The continual trend of conceptual to specifics throughout the book provides for an educational experience each time the book is either casually perused or carefully studied."" ""The authors (Cabrera, Haskins and Fritiz) diligently pursue the focus of improvement."" ""Benchmarking Water Services is an in depth and practical 'must have' guide for any utility currently engaged in or planning to develop a benchmarking process"" - Gregory M. Baird (2012) Benchmarking: An International Journal 19:2."